(untitled) (Proceedings of the World Conference on Waste Management, 2021)
Understanding waste flow of a country is important to identify main problems associated with waste management and identify opportunities in material flow management. Tools such as material flow analysis (MFA) is widely used method in waste management studies, to provide comprehensive analysis of material movements, support for material characterization analysis to identify severity of the problem, to identify real root cause and propose suitable management methods. This paper presents application of MFA for municipal solid waste (MSW) management in nine provinces in Sri Lanka. The outcome includes the identification, quantification of the main input and output flows of the system in present context, from waste generation, collection, unaccounted and unidentified flows, material recovery and final disposal of MSW. Overall results show per capita waste generation in Sri Lanka stood at 0.43kg, whereas Western province represents that of 0.53kg. On the other hand, 30% of the MSW is collected by the local authorities (institutional set up which is responsible for collecting waste in the country) out of total waste generation, 42% is burnt and 24% burry at house hold level. Balance represents composting and reusing - repurposing at house hold level. Results of this study show the importance of further research in unaccounted and unidentified material flows goes with burying and burning at household level. This can cause more harm to environment and human health